The Effect of Using The Learning Cycle Strategy on the Academic Achievement of Tenth Grade Students in Vocational Education in Jordan - Mohammad Omar AL-Momani; Elham Mahmoud Rababa (Faculty of Technological and Vocational Education-Universitas Pendidikan Indonesia, 2022)
The study aimed to recognise the effect of using a strategy learning cycle on the collection of school students. The tenth primary in vocational education in Jordan, where it was chosen as the High School for Boys in Governorate Ajloun, was chosen in two divisions In her school achievement of the people in tenth grade primary school, she randomly distributed these two divisions to form a control group and an experimental group. The first experimental group was taught it consists of 35 students using the learning cycle, While the subject was being taught, control sink It also consists of 35 students Using the usual traditional method to teach the two groups. Aqualified teacher to do this, the trial period lasted eight weeks. Statistical analyses of the study data revealed that in the second semester of school year 2021/2022 AD, there were statistically significant differences in the achievement of tenth grade students in material vocational education and those who were consoled to use teaching st rategy (learning cycle the traditional method); the differences in the collection were in favour of students who learned by the learning cycle strategy, compared to their peers who learned the traditional way.